Infrastructure and Economic Growth: Evidence from Indonesia - Annisa Farahmei Effnandya; Effnu Subiyanto; Aini Nur Febianti Effnandya (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: This study aims to examine the relationship between infrastructure spending and economic growth. Fundamental theories acknowledge that infrastructure activities simultaneously trigger significant funding circulation and open many opportunities as a machine to drive economic growth. Design/Methods/Approach: We employed several methods in a mixed-method technique to disclose this phenomenon. First, we extracted data and information through content analysis as initial findings. Second, we developed multiple approaches for confirmation and clarifying evidence, and appended sensitivity tests. Third, we constructed conclusions and recommendations. Findings: The findings are surprising, as the efforts of building massive infrastructure barely affected economic growth. It showed that infrastructure development effectively decreased logistics costs, but it was unable to leverage economic growth. Originality/Value: This study was primarily designed to examine Indonesia and thus should fit as the initial place of the investigation. We have excluded the possible impact of external influences caused by the outbreak of COVID-19, which was previously suspected to impede economic growth. Practical/Policy implication: The results of this study would be valuable as a consideration for the government to implement appropriate policies for infrastructure spending, especially during uncertain global economic development.